System Dynamics Model for Estimating Water Pollution - Sukruay, Jitlakha; Chaysiri, Rujira (INTERNATIONAL SCIENTIFIC JOURNAL OF ENGINEERING AND TECHNOLOGY (ISJET), 2019)
Water resources are essential for all living organisms. They are used for domestic consumption, agriculture, transportation, recreation, etc. Thus, water quality degradation is a global challenge, according to the United Nations (UN). This paper provides a system dynamics model that helps us see the interrelationships among water quality and the factors that affect it. The following are factors that influence the water quality in this model: national water policy, water and wastewater management, industrial growth, agricultural growth, population growth, and people’s awareness of health. These factors are grouped the three main sectors: household, industrial, and agricultural. This system dynamics model helps to generate an overview of the problem and see how each factor affects each other. Thus, this model contributes to improving the quality of water.